Metadata-Driven Software for Clinical Trials - Crichton, C; Davies, J; Gibbons, J; Harris, S; Tsui, A; Brenton, J; IEEE (2009)
The CancerGrid approach to clinical trials information systems is based on a metamodel developed from the CONSORT statement of best practice in reporting randomised controlled trials. The metamodel is instantiated with metadata elements drawn from a repository, to create a model of a particular clinical trial. The model is then used to derive automatically a trial management system customized for that trial: generating electronic case report forms, configuring randomisation and eligibility services, and parameterising the security subsystem. The key benefits of the approach are a uniform mechanism for trial registration and discovery, reduced cost and rapid implementation of information systems, and shared semantics leading to improved opportunities for meta-analysis. We describe our implementation of this approach, and outline two applications: for a breast cancer study in the UK, and for a rheumatoid arthritis study run by the US Veterans' Health Administration. © 2009 IEEE.